Exchange Rates of Creatine Kinase Metabolites: Feasibility of Imaging Creatine by Chemical Exchange Saturation Transfer MRI - Haris, Mohammad (2012)
Creatine (Cr), phosphocreatine (PCr) and adenosine-5-triphosphate (ATP) are the major metabolites of the enzyme creatine kinase (CK). The exchange rate of amine protons of CK metabolites at physiological conditions has been limited so far. In the current study, the exchange rate and logarithmic dissociation constant (pKa) of amine protons of CK metabolites were calculated. Further, the chemical exchange saturation transfer effect (CEST) of amine protons of CK metabolites with bulk water was explored. At physiological temperature and pH, the exchange rate of amine protons in Cr was found to be 7–8 times higher than PCr and ATP. Higher exchange rate in Cr is associated with lower pKa value suggesting the faster dissociation of its amine protons when compared to PCr and ATP. CEST MR imaging of these metabolites in vitro in phantoms displayed predominant CEST contrast from Cr and negligible contribution from PCr and ATP with the saturation pulse parameters used in the current study. These results provide a new method to perform high resolution proton imaging of Cr without any contamination from PCr. Potential applications of these finding in biomedical imaging are discussed.